Women's Empowerment, the Gender Gap in Desired Fertility, and Fertility Outcomes in Developing Countries - Matthias Doepke; Michèle Tertilt (Institute of Labor Economics (IZA), 2018)
We document evidence on preferences for childbearing in developing countries. Across countries, men usually desire larger families than women do. Within countries, we find wide dispersion in spouses' desired fertility: there are many couples whose ideal family size differs by five children or more. This disagreement between spouses suggests that the extent to which women are empowered should matter for fertility choices. We point to evidence at both the macro and micro levels that this is indeed the case. We conclude that taking account of household bargaining and women's empowerment in analyses of fertility is an important challenge for research.
Keywords: J12; J13; J16; O10; 330; women's empowerment; desired fertility; marital bargaining